DAMPAK PROMOSI, KUALITAS DAN KETERSEDIAAN PRODUK TERHADAP KEPUASAN PELANGGAN SARI ROTI PADA INDOMARET - Henrizal, Henrizal; Diantara, Litra; Setiawan , Adi; Azhari, Azhari; Tanjung, Irfan (Komunitas Manajemen Kompetitif, 2025)
This research was carried out with the aim of promotion, quality and product availability having a simultaneous and partial effect on Sari Roti customer satisfaction at Indomaret in Bangkinang. Sampling in this research was using the Lemeshow formula, which is used to calculate the number of samples because the population is unlimited, the research sample is 96 respondents. The data collection method used was distributing questionnaires. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. The research results concluded that partially Product Quality and Availability had a significant effect on Customer Satisfaction, while Promotion had no significant effect on Customer Satisfaction. The Adjusted R Square value is 0.848. This means that the contribution of the Promotion, Quality and Product Availability variables to the Customer Satisfaction variable is 84.8%